Casing a promised land : the autobiography of an organizational detective as cultural ethnographer - Goodall, H. Lloyd (Southern Illinois University Press, 1994)
H.L. Goodall's ground-breaking study of what people do with symbols and what symbols do to people explores the lives led by people in organizations. His narratives take on the form of six detective mysteries in which the narrator figures into the plot of the intrigue and then works out its essential patterns. In the first mystery, ""Notes on a Cultural Evolution: The Remaking of a Software Company, "" Goodall looks at the transition of a Huntsville regional office of a Boston-based computer software company where the lives and social dramas of the participants reflect the current state of hi